Social and ritual networks in Southeast China during the seventeenth and eighteenth centuries - Scarin, Jacopo (Studies in Chinese Religions, 2022)
This article studies the Longmen Daoist communities of the Jiangnan area during the seventeenth and eighteenth centuries and it focuses especially on the social networks established there in the context of ritual training. The common representation of Quanzhen Daoists, including that of the Longmen branch, describes them as eminently interested in self-cultivation. This idea is not unfounded, but the analysis of coeval sources, produced both within and outside the Daoist milieus, reveals that those Daoists were also proficient ritualists. More importantly, ritual training within these communities appears to have sometimes relied on Daoist masters initiated both into the Longmen and the Zhengyi traditions as liturgical teachers for other Longmen Daoists. The second part of the article expands the focus of the study, suggesting the existence of a link between the regional liturgical traditions of Jiangnan and the broader religious landscape of late imperial China, effectively connecting the ritual curriculum of Longmen Daoists with court Daoism.